Participação da neurotransmissão orexinérgica nas respostas respiratórias à hipercarbia e hipóxia em sapos - Fonseca, Elisa Maioqui (Universidade Federal de São Carlos, 2014)
The hypocretin or orexin A plays an important role in the modulation of respiratory control in mammals, but there are no data available for the role of Orexins in the peripheral and central chemoreception of non-mammalian vertebrates. Thus, the present study was designed to evaluate the location of orexinergic neurons in toads (Rhinella schneideri). In addition, we investigate if the orexinergic system of this species is important to hypoxic (5% O2 and N2 for balance) and hypercarbic (5% CO2, 21% O2 and N2 for balance) drive to breath. We assessed the role of the orexinergic system on respiratory responses by using intracerebroventricular injection of SB-334867 (orexin A receptor antagonist) during the light and the dark phase. Our results demonstrated that orexinergic neurons of Rhinella schneideri are located in the suprachiasmatic nucleus of diencephalon. Additionally, the injection of the orexin antagonist attenuated the ventilatory response to hypercarbia during the dark phase by acting on tidal volume and breathing frequency, while in the light phase, there was an attenuation in the ventilatory response to hypoxia by acting just in the tidal volume. We conclude that central orexin A contributes to hypercarbic and to hypoxic chemoreflex in toads Rhinella schneideri.
Keywords: Orexina; Hipercarbia; Hipóxia; Ventilação pulmonar; Anfíbio; Quimiorrecepção; Sapo; Orexin; Chemoreception; Ventilation; Amphibian; Toad; CIENCIAS BIOLOGICAS::FISIOLOGIA